Law Enforcement Experience with Illegal Drugs and Its Influence on Police Officer Perceptions of Illegal Drugs, Their Users, and the Market That Furnish These Drugs - Pascale, Bourque (Université d'Ottawa / University of Ottawa, 2018)
Illegal drug use is perceived as immoral, criminogenic, and an unhealthy practice for decades under the discourse sustaining drug prohibition. Those who apply prohibition laws on the front lines are narcotic police officers, particularly the ones who work in narcotic squads. Based on the specific context in which these individuals work in, perceptions and meanings on drug prohibition and illegal drug use will emerge. This project will explore drug enforcement officer’s perceptions on Canadian drug legislation and illegal drug use through the mobilization of Maurice Merleau-Ponty’s interpretation of phenomenology and social problems theory.
Keywords: Prohibtion; Police Officer; Perceptions; Illegal Drugs; Phenomenology; Cannabis